2010
DOI: 10.1002/hfm.20228
|View full text |Cite
|
Sign up to set email alerts
|

Ergonomic planned supply in an automotive assembly line

Abstract: The objective of this research is to identify the benefits of ergonomic improvements in workstations and in planned parts supply in an automotive assembly line. Another aim is to verify to what extent it is possible to create competitive advantages in the manufacturing area with reduction in vehicle assembly time by using technological investments in ergonomics with benefits to the worker and to the company. The Methods Time Measurement (MTM) methodology is chosen to measure the process time differences. To en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 15 publications
(12 reference statements)
0
5
0
1
Order By: Relevance
“…The new assembly line had 30% fewer quality errors compared to the traditional assembly line. Assembly time and absenteeism on the new ergonomic assembly line were also lower (Baraldi & Paulo, ). The interactions between various ergonomic interventions and also their exclusive impact on quality were not investigated in this study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The new assembly line had 30% fewer quality errors compared to the traditional assembly line. Assembly time and absenteeism on the new ergonomic assembly line were also lower (Baraldi & Paulo, ). The interactions between various ergonomic interventions and also their exclusive impact on quality were not investigated in this study.…”
Section: Resultsmentioning
confidence: 99%
“…() reported that design engineers overlooked the consequences of poor product design on the difficulty of assembly, ergonomic workloads, and quality. Baraldi and Paulo () compared two automotive assembly lines, the first of which was new, with high ergonomic investment in design and organization, and the second was traditional with low consideration of ergonomics. The new assembly line had 30% fewer quality errors compared to the traditional assembly line.…”
Section: Resultsmentioning
confidence: 99%
“…Considerar o investimento em equipamentos auxiliares que diminuam os esforços físicos e evitem os movimentos mais agressivos dos operadores é tão importante quanto a garantia da qualidade e demais características técnicas do produto. Melhores condições de trabalho e ergonomia do trabalhador tendem a reduzir os afastamentos por problemas de saúde, proporcionar benefícios à produção e ao produto [17], [18], além de evitar problemas judiciais entre empregado e empregador. …”
Section: Desenvolvimento Do Processo De Fabricação E Manufaturaunclassified
“…One of the most popular PTS is the Methods-Time Measurement (MTM) process building block system (Genaidy, Agrawal, & Mital, 1990). The MTM process language is widely employed for consistent productivity management within the value chain, for modeling human movements and the design of productive as well as healthy work conditions (e.g., Baraldi & Kaminski Paulo, 2011;Busenbach, Link, Füssel, & Ortner, 2011;Das, Shikdar, & Winters, 2007;Zandin, 2001). The required time for a certain task is determined by dividing manual operational procedures into elements of motions and considering the work conditions simultaneously.…”
Section: Introductionmentioning
confidence: 99%